Aspek Hukum Kepegawaian Bagi Perawat Yang Ditempatkan di Sterilisasi Sentral - Prihaningsih, Lilies; Yusan, Liza Yudistira (Verdict: Journal of Law Science, 2024)
The Centralized Sterilization Installation has a strategic role in preventing infections in the hospital environment. However, its existence has not been properly regulated by law. The purpose of this study was to analyze the rule of law for placing nurses in the Central Sterilization Installation in hospitals and to analyze the legal protection for nurses who were placed in the Central Sterilization Installation regarding career development opportunities. This research is a normative juridical research using a statutory and conceptual approach. From the results of the research, it can be concluded: First, legal arrangements regarding CSSD installations are still general and abstract in nature which still require elaboration through lower, more concrete and technical legislation. However, until now there are no more concrete and technical regulations, so there is still a legal vacuum that can create legal uncertainty. Second, nursing staff with the status of civil servants are required to comply with being willing to be placed in other positions with consideration for the interests of the organization and nurse career development. However, the placement of nurses in CSSD installations actually hampers their opportunities for career development, because they have the lowest credit score This is due to the fact that certain functional positions have not been assigned to the CSSD installation. Through research, government agencies should immediately assign specific positions to health workers assigned to CSSD Installations so that they do not overlap with functional positions for health workers transferred to CSSD Installations.